Milling parameter optimization for the refinement of NiO/Al mixtures and the synthesis of Ni/Al2O3 nanocomposites - Berramdan N E.H.; Boutefnouchet H.; Zidani M.; Yamanoglu R.; Curfs C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This study examined the effects of milling parameters on the development of Ni/Al2O3 nanocomposites and the refinement of NiO and Al powders. Ball milling of certain mixtures was followed by sintering at 800 and 1100 °C for 2 h. The X-ray diffraction results of the dry-milled powders indicated that increasing the ball-to-powder weight ratio from 20:1 to 42:1 resulted in finer particles, which enabled the synthesis of Ni/Al2O3 nanocomposites by milling at 200 rpm for 1.5 h. Extending the milling duration at lower rotational speeds yielded powders with nanoscale particle sizes. However, as shown by scanning electron microscopy and energy dispersion spectroscopy, a nanocomposite with metallic matrix was formed by the mechanochemical reaction, and the crystallite size was estimated using the Williamson–Hall plot. Furthermore, we used differential scanning calorimetry diagrams to analyze the effects of milling on the temperatures of phase transformation and/or reduction reactions. The tribological performance of the developed nickel metal matrix composite was investigated using a ball-on-disc tribometer under various loading conditions. Indeed, the friction coefficient increases with the applied forces and decreases with milling. Comprehensive examinations of the worn surfaces were carried out using a scanning electron microscope and a 3D optical profiler.